The Role of Interpersonal Chemistry in Small Teams A case study of three small teams with a creative main task - AGNES, NERELIUS (My University, 2020)
Small teams are present in many situations in the society as a whole, and the decision making impacts these teams and their dynamics more directly than their larger counterparts. These dynamics can influence the potential creativity of the team since there are different factors that influence team creativity related to its dynamics. The decision making within the teams is influenced by emotions that the initial instincts evoke in a person, and these emotions are partly formed by the interpersonal chemistry between individuals. It is therefore interesting to look at the interpersonal chemistry’s impact on team dynamics in small teams with a creative main task. The aim of this thesis is to investigate the role of interpersonal chemistry in small teams with highly educated team members, which primary task is creative. A qualitative research based on interviews and participant observations of three different teams was conducted. The major findings were that there are quick results and large impacts of decisions made and implemented in small teams. These decisions are primarily based on intuition and emotion, and strategic reasoning comes secondary as a motivation for the immediate reactions. These emotions also tap into and are important in interpersonal chemistry and the connection between individuals. These results show a link between small teams and interpersonal chemistry and decision making, since they indicate that interpersonal chemistry is important in small teams seeing that it impacts the decisions and the decisions are very noticeable in this type of team. Furthermore, a team’s constellation and dynamics are a direct result from the interpersonal chemistry and the initial perceptions it brings from initial interactions between the leader and potential team members. Additionally, the interpersonal chemistry between individuals will impact their emotions, and emotions are the foundation for many of our decisions. These decisions will in turn affect the team dynamic of the teams we belong to.
Keywords: Interpersonal chemistry; small creative teams; group dynamics; decision making